Peran Badan Pengawas Pemilu pada Pemilihan Umum Kepala Daerah Serentak di Kabupaten Tasikmalaya Tahun 2024 - Ade Elsa Nuranisa; Arie Budiawan; Neti Sunarti (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study was to determine the Role of the Election Supervisory Body in the Simultaneous Regional Head Elections in Tasikmalaya Regency in 2024. The method used in this study is a qualitative descriptive research method. This method includes observation, interviews and documentation. Data processing techniques in this study are data reduction, data presentation, and drawing conclusions. The results of the study show that the role of the Election Supervisory Body (Bawaslu) has not been running optimally as seen from four dimensions. First, in the dimension of the role as an entrepreneur, Bawaslu experienced obstacles in understanding organizational issues and building relationships with the KPU, which was caused by miscommunication and weak supervision which led to a Revote. Second, in the dimension of the role as a disturbance handler, Bawaslu has not been effective in dealing with unexpected problems, hampered by the pros and cons of the community and the lack of formal and material evidence to follow up on reports of alleged violations. Third, in the dimension of the role as a resource allocator, the use of funding sources has not been optimal because the Revote resulted in the use of previous funds being inefficient. Finally, in terms of its role as a negotiator, Bawaslu has not been effective when participating in negotiations because it often takes a long time. The efforts that must be made are to strengthen communication and coordination between Bawaslu and the KPU, increase transparency and supervision during the election process, improve the system for collecting evidence of alleged violations and accelerate the negotiation process so that the decision-making process runs more efficiently. Based on the results of the study above, it can be concluded that the Role of the Election Supervisory Body in the Simultaneous Regional Head Elections in Tasikmalaya Regency in 2024, overall, is still not running optimally.